Ophioderma hendleri sp. nov. (Echinodermata: Ophiuroidea: Ophiodermatidae) and its congeners from the Eastern Pacific - Granja-Fernández, Rebeca; Pineda-Enríquez , Tania; Solís-Marín, Francisco Alonso; Laguarda-Figueras, Alfredo (European Journal of Taxonomy, 2020)
The widespread Ophioderma hendleri sp. nov., from the Eastern Tropical Pacific (Mexico to Colombia) is distinguished from its congeners by having radial shields covered by granules, naked adoral shields, up to 11 arm spines, and by its brown and beige coloration. Ophioderma hendleri sp. nov. belongs to the group of species with naked adoral shields (i.e., O. pentacanthum H.L. Clark, 1917, O. variegatum Lütken, 1856), and it has frequently been misidentified as O. panamense Lütken, 1859 or O. variegatum. Therefore, the main aim of the present work was to describe Ophioderma hendleri sp. nov. and differentiate it from its congeners. The original description of O. panamense was incomplete; thus, we provide a redescription. Due to the confusion in previous designations of its type material, we designate a lectotype and paralectotype of O. variegatum. Finally, we expand the distribution range of O. pentacanthum to Cocos Island, Costa Rica. With this work, the total number of valid species of Ophioderma Müller & Troschel, 1840 in the world increases to 33 and in the Eastern Pacific to nine species.